Pengaruh Intellectual Capital Disclosure Dan Leverage Terhadap Cost Of Equity Capital - Gita Septiani; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to examine and find empirical evidence regarding the effect of intellectual capital (and its three aspects : human capital, relational capital & structural capital) disclosure and leverage on cost of equity capital.The population in this study were all property and real estate sector companies listed on the Indonesia Stock Exchange in 2014-2017. By using a purposive sampling technique obtained as many as 39property and real estate sector companies that will be used as research samples. The data analysis method used is pooled regression analysis. The results showed that intellectual capital disclosure and its three aspects don’t have significant negative effect on cost of equity capital and leverage does not have a significant positive effect on cost of equity capital in property and real estate sector companies listed on the Indonesia Stock Exchange in 2014-2017